An overview of swine production and marketing in Africa - Mini review - Owusu, Desmond; Osotsi, Joab Malanda; Novotni-Dankó, Gabriella (Acta Agraria Debreceniensis, 2024)
Pigs are the oldest domesticated animals, though their ancestry is still uncertain because of a lack of archaeological and genetic evidence. Pigs serve a vital role in reducing the demand for livestock and livestock products in most parts of the world. Especially in the African continent, pigs serve as mobile cash implying how easily they can be converted into cash to sort pressing family needs. Pig production in Africa is different from advanced systems of production in temperate countries, however, it has similarities with most of the tropical low and middle-income nations. Pig production in Africa requires attention to enable it to contribute effectively to the growing African population. However, it has been orchestrated with a myriad of challenges including market access. This mini-review is designed in a manner to provide an overview of pig production contribution to livelihoods in Africa and associated challenges with possible appropriate solutions.